Correlation and path coefficient analysis in sweet pepper (Capsicum annuum L.) grown under greenhouse conditions - Monge-Pérez, José Eladio (2021)
For 27 sweet pepper genotypes grown under greenhouse conditions the researchers estimated Pearson correlations among twelve variables:  plant height (PH), leaf area (LA), stem diameter (SD), stem length (SL), fruit length (FL), fruit width (FW), fruit length/width ratio (FL/FW), pericarp thickness (PT), number of fruits per plant (NFP), days to start of harvest (DSH), first quality fruit weight (FQFW), and commercial yield (CY).  Also, path analysis was estimated for CY.  CY showed a positive and significant correlation with NFP (r=0,51**), FL (r=0,40*) and FL/FW (r=0,39*).  The main positive direct effects on CY were exhibited by NFP (path coefficient-PC=1,78), FQFW (PC=0,73), FW (PC=0,70), FL (PC=0,62), PT (PC=0,31) and PH (PC=0,26), while maximum positive indirect effects on CY were exhibited by LA (PC=1,37), FL/FW (PC=1,29), PH (PC=1,17), SL (PC=1,13) and FL (PC=1,01) through NFP.  On the other hand, the main negative direct effects on CY were exhibited by SD (PC=-0,37), SL (PC=-0,24), DSH (PC=-0,22) and LA (PC=-0,18).  Results from correlation and path analysis showed that efficiency in selection for CY in sweet pepper may be increased through selection of NFP.  It is concluded that NFP was the main CY contributing variable in these trials, and thus represents a fundamental selection criteria for greenhouse sweet pepper breeding.  Other important variables to consider are FL and FL/FW.